The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.amsu.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among surgical residents in a lower-middle income country - Are we any different?

Abstract: ObjectiveTo assess the presence of burnout among surgical residents working at various public sector hospitals in Pakistan.DesignA survey based on MBI was used to assess the presence of burnout. Residents were grouped into Group A (Burn out) or Group B (No burn out). Pearson Test was used to see any correlation between different variables and burn out. A p value of <0.05 was taken as significant.Setting/participantsA cross sectional survey of all the surgical residents at various public sector hospitals in Lah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 24 publications
7
31
0
3
Order By: Relevance
“…These values are relatively higher compared to a survey reporting 57.9% rate of overall burnout among surgical residents. 17 Similarly, our study puts the overall rate of burnout among gynecologists at 75%-a higher figure compared to previous reports from Pakistan, which showed that 44.1% of gynecological residents were dissatisfied with their career choice. 8 Our study also reports increased risk of burnout among ophthalmological residents and consultants-a prospect hitherto unexplored in Pakistan.…”
Section: Discussionsupporting
confidence: 45%
“…These values are relatively higher compared to a survey reporting 57.9% rate of overall burnout among surgical residents. 17 Similarly, our study puts the overall rate of burnout among gynecologists at 75%-a higher figure compared to previous reports from Pakistan, which showed that 44.1% of gynecological residents were dissatisfied with their career choice. 8 Our study also reports increased risk of burnout among ophthalmological residents and consultants-a prospect hitherto unexplored in Pakistan.…”
Section: Discussionsupporting
confidence: 45%
“…The heterogeneity chi-squared was 609.75 (p<0.001) with an I 2 statistic of 96.9%. This comparison of the proportion of residents presenting burnout between all types of specialties suggests that the specialties are distributed into three groups with different levels of the syndrome: a group composed of general surgery,[ 41 , 42 ] anesthesiology,[ 51 ] obstetrics and gynecology,[ 31 35 ] and orthopedics[ 38 , 39 ] with a high prevalence of 42.5%; a group formed by internal medicine,[ 45 49 ] plastic surgery[ 40 ] and pediatrics,[ 36 , 37 ] with a moderate prevalence of 29.4%; and finally a group including otolaryngology[ 25 , 30 ] and neurology,[ 16 ] with a low burnout syndrome prevalence of 23.5% ( Fig 2 ). However, no statistically significant difference was found by meta-regression (p = 0.17).…”
Section: Resultsmentioning
confidence: 99%
“…While there are several studies describing coping strategies used by medical professionals, techniques specifically used by surgical trainees to help them cope with their lengthy training period are less well described. Four studies were identified that discuss strategies used by trainees to help them cope with stress and burnout . Descriptions of the coping strategies employed by trainees is provided in Tables S1 and S2.…”
Section: Coping Strategies Are Used By Surgical Traineesmentioning
confidence: 99%